Mining law in Aotearoa New Zealand - Wagner, Estair Van; Bargh, Maria (Decolonizing Law, 2021)
Minerals in Aotearoa New Zealand are regulated by the Crown Minerals Act, 1991 (the CMA). Like other statutes in New Zealand, the CMA recognizes Te Tiriti o Waitangi (the Treaty of Waitangi), signed by the British and Māori in 1840, and therefore the relationship between Māori and the lands and resources governed by the Act. The Treaty relationship continues to play a crucial role in conflicts about land and resources and is central to the practice of decolonization for Māori. However, as we argue, the governance of relationships between people and minerals, as foundational elements of material systems, extend much further to the Māori legal orders developed throughout Aotearoa.

Participation as exclusion: Māori engagement with the Crown Minerals Act 1991 Block Offer process - Bargh, Maria; Wagner, Estair Van (Journal of Human Rights and the Environment, 2019)
Land and natural resources are at the core of conflicts between Indigenous peoples and Settlers in settler-colonial nations. This article explores the coloniality of natural resource law in the context of the New Zealand Crown Minerals Act 1991 (CMA) Block Offer process; the annual tender process for mineral prospecting and exploration. While there is often strong Māori participation, we will argue that Aotearoa New Zealand settler-colonial mining law is structured in such a way that Māori views rarely influence the substantive outcomes of mineral exploration decisions. Through a case study of the 2013 Epithermal Gold Block Offer in the Central North Island, we will explore the factors that might contribute to the mismatch between the level of Māori participation and the influence of Māori views on final decisions in the Block Offer process. We examine how different views are valued by bureaucrats within New Zealand Petroleum and Minerals, a government agency within the Ministry of Business, Innovation and Employment, and explore whether the criteria applied to Māori submissions genuinely and appropriately reflect the full range of interests, aspirations and concerns raised by Māori participants. In particular, we consider how mining regulation is structured to exclude Māori law and jurisdiction in order to uphold settler-colonial authority over key natural resources and extractivist economies. Finally, we consider alternatives to the CMA process and explore the potential to ensure substantive outcomes that better reflect the Māori views and interests. In doing so we point to the need to shift from colonial extractivist models of natural resources law towards Settler-Indigenous partnerships in relation to environmental planning in settler-colonial states.
Keywords: crown policy; land policy

Unearthing (de)colonial legal relations: Mining law in Aotearoa New Zealand - Bargh, Maria; Wagner, Estair Van (Decolonizing law: Indigenous, third world and settler perspectives, 2021)
Keywords: colonisation; crown policy; decolonisation; environment; tiriti o waitangi/treaty of waitangi